Impact of Tin Mining on Soil Physio-Chemical Properties in Bangka, Indonesia - Wulandari, Dewi; Agus, Cahyono; Rosita, Risa; Mansur, Irdika; Fikri Maulana, Ahdiar (Jurnal Sains dan Teknologi Lingkungan, 2022)
Surface mining, including tin mining, is the most common mining practice in Indonesia. The existence of mining ore or minerals close to the surface soil is the reason for carrying out this mining method. The process of mining surface resulted in the change of land landscape, which may cause soil erosion and even flood. It has caused various ecological and environmental problems, including soil degradation. This study describes soil physio-chemical properties impacted by surface tin mining in Bangka, Indonesia. Soils were collected from three different land use in natural forest, agroforestry, and post tin mining area in Bangka Regency, Province of Bangka Belitung Island. Five-spot soils were sampled from each site. Each site had three replication of the sampling area. The plot size for each site is about 200-500 m2. Soil texture, pH, total N, available P, exchangeable K, organic carbon, C/N ratio, CEC, Al3+, and H+ were analyzed. The results showed that mining decreased organic carbon, total N, available P, exchangeable K, and CEC. Mining changed the soil texture to be dominated by quartz sand. These results indicate that mining significantly deleterious soil fertility, therefore, potential as a limiting factor for plant growth, which could be a hamper for restoration efforts of post tin mining areas. Keywords: tin mining, restoration, soil physiochemical properties, soil degradation